Differences in estimation of sugarcane phenotypic parameters using unmanned aerial vehicle multispectral and hyperspectral data - Chen Yanli; Huang Lu; Yang Shaoe; Sun Ming; Ding Meihua; Huang Lining; Ma Ruisheng; Liang Chi; Yang Xin; Chen Cheng (Computers and Electronics in Agriculture, 2026)

Seasonal variation shapes microbial succession and volatile flavor profiles during the production of strong-flavor Daqu - Jialiang Niu; Xi Chen; Xucheng Zhu; Weiwei Li; Huifeng Ma; Lining Zhu; Xiuting Li; Weizheng Sun; Baoguo Sun (Food Research International, 2026)

Muscle Organoids Frontier: Construction Strategies and Applications of Multi-lineage Muscle Organoids and Multi-organoid Systems - Dingding Wang; Lining Xu; Weijia Liu; Zitong Xie; Yuqing Sun; Mingxing Fan; Ling Wang; Quanzhong Ren; Yajun Liu; Junbo Liang; Renxian Wang (Phenomics, 2026)

A self-sustained and self-sensing ocean observation buoy: System integration and in-situ sea trial - Yunfei Li; Tianyi Tang; Heng Zhao; Lining Sun; Fusheng Zha; Huicong Liu (Ocean Engineering, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Identification of novel B-cell epitopes on Hirame novirhabdovirus (HIRRV) G protein and development of a multi-epitope vaccine - Pingyuan Sun; Lining Zhao; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2026)

Anthropogenic fire suppression and climate change-driven winter warming inducing the dieback of natural Pinus sylvestris var. mongolica forests on sandy land - Lining Song; Mingxi Zhang; Jiaojun Zhu; Yirong Sun; Xiao Zheng; Xiaolin Zhang (Forest Ecology and Management, 2026)

Impact of secondary temperature rise on microbial succession and flavor compounds in strong-flavor baijiu fermentation - Xi Chen; Haideng Li; Fanghang Qiu; Jialiang Niu; Akhtiar Ali; Lining Zhu; Huifeng Ma; Weiwei Li; Xiuting Li; Baoguo Sun (Food Research International, 2025)

Assessing the ecological effects of the World’s Largest Forestry Eco-engineering: Three-North Protective Forest Program within the initially scheduled range from 1978 to 2022 - Xiao Zheng; Jiaojun Zhu; G. Geoff Wang; Qiaoling Yan; Tao Sun; Lining Song; Tian Gao; Yirong Sun; Xiufen Li; Kai Yang; Jinxin Zhang; Lizhong Yu; et al. (Science China Life Sciences, 2025)

Intestinal microbiota was closely related to feed efficiency of Larimichthys crocea fed two fishmeal-free diets - Xiaotong Li; Gongsi Wang; Ranxin Fu; Xingcheng Zhu; Peng Ren; Lining Zhang; Qinghui Ai; Yunzhang Sun; Zhiyong Wang (Aquaculture, 2025)

The performance of a spark ignition gasoline engine with hydrogen addition under low-load conditions - Xiongbo Duan; Lining Feng; Xianghe Chu; Zhiqiang Sun (Fuel, 2025)

lncTIMP3 promotes osteogenic differentiation of bone marrow mesenchymal stem cells via miR-214/Smad4 axis to relieve postmenopausal osteoporosis - Taxi Wumiti; Lining Wang; Bin Xu; Yong Ma; Yihua Zhu; Xinchen Zuo; Weiqing Qian; Xudong Chu; Haitao Sun (Molecular Biology Reports, 2024)

Flexible and rapid generation of multiple concentration gradients for the protein nanoparticle synthesis - Haoyang Lu; Zihan Zhou; Haoyang Ping; Haizhen Sun; Lining Sun; Tao Chen (Chemical Engineering Journal, 2024)

Investigation of the efficacy of graphite-sulfur iron tailing composite catalysts for activation of peroxydisulfate for rhodamine B degradation - Zhongbin Lv; Haojie Che; Jie Mao; Yuqi Feng; Bai Sun; Liping Xue; Jian Wang; Yun Wan; Lining Bao; Shuguang Zhu (Environmental Science and Pollution Research, 2024)

Metformin modulates mitochondrial autophagy in renal tubular epithelial injury induced by high glucose via the Keap1/Nrf2 pathway - Da Sun; Huimin Li; Yinke Du; Ying Chen; Li Yao; Lining Wang (Molecular and Cellular Biochemistry, 2024)

Transpiration and water use sources of poplar (Populus × xiaozhuanica) plantations with 7-years vs. 20-years old in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xin Liu; Jinxin Zhang; Xiao Zheng; Yirong Sun; Guochen Wang; Linyou Lü (Agricultural and Forest Meteorology, 2024)

Effects of Saccharomyces cerevisiae on microbial community and flavor metabolites in solid-state fermentation of strong-flavor Baijiu - Fanghang Qiu; Binghao Du; Chengnan Zhang; Lining Zhu; Yatao Yan; Weiwei Li; Weijun Leng; Zemin Pang; Xiuting Li; Baoguo Sun (Food Bioscience, 2024)

Microbial community dynamics and spatial distribution of flavor compound metabolism during solid-state fermentation of Baijiu enhanced by Wickerhamomyces anomalus - Qiuxiao Li; Binghao Du; Xi Chen; Yanan Zhao; Lining Zhu; Huifeng Ma; Baoguo Sun; Jianxiong Hao; Xiuting Li (Food Bioscience, 2024)

RGB/Event signal fusion framework for multi-degraded underwater image enhancement - Xiuwen Bi; Pengfei Wang; Wei Guo; Fusheng Zha; Lining Sun (Frontiers in Marine Science, 2024)
Underwater images often suffer from various degradations, such as color distortion, reduced visibility, and uneven illumination, caused by light absorption, scattering, and artificial lighting. However, most existing methods have focused on addressing singular or dual degradation aspects, lacking a comprehensive solution to underwater image degradation. This limitation hinders the application of vision technology in underwater scenarios. In this paper, we propose a framework for enhancing the quality of multi-degraded underwater images. This framework is distinctive in its ability to concurrently address color degradation, hazy blur, and non-uniform illumination by fusing RGB and Event signals. Specifically, an adaptive underwater color compensation algorithm is first proposed, informed by an analysis of the color degradation characteristics prevalent in underwater images. This compensation algorithm is subsequently integrated with a white balance algorithm to achieve color correction. Then, a dehazing method is developed, leveraging the fusion of sharpened images and gamma-corrected images to restore blurry details in RGB images and event reconstruction images. Finally, an illumination map is extracted from the RGB image, and a multi-scale fusion strategy is employed to merge the illumination map with the event reconstruction image, effectively enhancing the details in dark and bright areas. The proposed method successfully restores color fidelity, enhances image contrast and sharpness, and simultaneously preserves details of the original scene. Extensive experiments on the public dataset DAVIS-NUIUIED and our dataset DAVIS-MDUIED demonstrate that the proposed method outperforms state-of-the-art methods in enhancing multi-degraded underwater images.

Microfluidic device featuring micro-constrained channels for multi-parametric assessment of cellular biomechanics and high-precision mechanical phenotyping of gastric cells - Yang Heng; Xinyu Zheng; Youyuan Xu; Jiaqi Yan; Ying Li; Lining Sun; Hao Yang (Analytica Chimica Acta, 2024)

Multi-scale free oscillations and resonances over the continental shelf of the East China Sea from the 2011 Tohoku-Oki tsunami - Peitao Wang; Wei Lu; Yuchen Wang; Zongchen Wang; Jingming Hou; Lining Sun (Ocean Modelling, 2024)

Multilevel nanostructured pressure sensor for object recognition with Deep-Learning assistance: A strategy for high sensitivity and wide detection range - Yexi Jin; Hao Shen; Lining Sun; Xingwen Zhou; Liguo Chen (Chemical Engineering Journal, 2024)

A Review of Historical Volcanic Tsunamis: A New Scheme for a Volcanic Tsunami Monitoring System - Tingting Fan; Yuchen Wang; Zhiguo Xu; Lining Sun; Peitao Wang; Jingming Hou (Journal of Marine Science and Engineering, 2024)
Tsunami monitoring and early warning systems are mainly established to deal with seismogenic tsunamis generated by sudden seafloor fault displacement. However, a global tsunami triggered by the 2022 Tonga volcanic eruption promoted the need for tsunami early warning and hazard mitigation of non-seismogenic tsunamis in coastal countries. This paper studied the spatiotemporal distribution characteristics of historical volcanic tsunamis and summarized high-risk areas of volcanic tsunamis. The circum southwestern Pacific volcanic zone, including the Sunda volcanic belt and the Indo-Australian plate, is a concentrated area of active volcanoes and major volcanic tsunamis. In addition, the challenges associated with adapting seismogenic tsunami techniques for use in the context of volcanic tsunamis were elucidated. At the same time, based on historical records and post-disaster surveys, typical historical volcanic tsunami events and involved mechanisms were summarized. The results show that a majority of volcanic tsunamis may involve multiple generation mechanisms, and some mechanisms show geographical distribution characteristics. The complexity of volcanic tsunami mechanisms poses challenges to tsunami early warning by measuring tsunami sources to evaluate the possible extent of impact, or using numerical modeling to simulate the process of a tsunami. Therefore, a concise overview of the lessons learned and the current status of early warning systems for volcanic tsunamis was provided. Finally, a conceptual scheme of monitoring systems for volcanic tsunamis based on historical volcanoes, real-time volcanic eruption information and sea level data, as well as remote sensing images, was presented.

Modulation of glucose metabolism through macrophage-membrane-coated metal-organic framework nanoparticles for triple-negative breast cancer therapy - Qing Yao; Jinyao Ye; Yahui Chen; Lihui Huang; Lining Sun; Zhinan He; Jianing Wu; Yingyi Zhao; Xinyu Zhao; Aimin Cai; Xiandan Chen; Hailun Zheng; et al. (Chemical Engineering Journal, 2024)

Exposure to outdoor artificial light at night increases risk and burden of metabolic disease in Ningxia, China - Huihui Wang; Xiaohong Ma; Zhenfan Yu; Naifan Hu; Yurun Du; Xiaoxue He; Degong Pan; Lining Pu; Xue Zhang; Xian Sun; Jiangping Li (Environmental Science and Pollution Research, 2023)

How did the Tonga volcanic tsunami on January 15, 2022, affect Chinese coasts? - Zongchen Wang; Zhiguo Xu; Ye Yuan; Huaiwei Yang; Lining Sun; Peitao Wang; Tingting Fan (Science China Earth Sciences, 2023)

The potential meat flavoring generated from Maillard reaction products of wheat gluten protein hydrolysates-xylose: Impacts of different thermal treatment temperatures on flavor - Ao Sun; Lining Chen; Wei Wu; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Food Research International, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

An efficient method to improve travel time delays of transoceanic tsunamis based on depth-correction scheme - Peitao Wang; Lining Sun; Lianda Zhao (Ocean Dynamics, 2022)

Transpiration of Pinus sylvestris var. mongolica trees at different positions of sand dunes in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xinjunyan Li; Kai Wang; Guochen Wang; Haihong Sun (Trees, 2022)

Insights on the small tsunami from January 28, 2020, Caribbean Sea MW7.7 earthquake by numerical simulation and spectral analysis - Zhiguo Xu; Lining Sun; Mohd Nashriq Abd Rahman; Shanshan Liang; Jianyu Shi; Hongwei Li (Natural Hazards, 2022)

Observations and modelling of the travel time delay and leading negative phase of the 16 September 2015 Illapel, Chile tsunami - Peitao Wang; Zhiyuan Ren; Lining Sun; Jingming Hou; Zongchen Wang; Ye Yuan; Fujiang Yu (Acta Oceanologica Sinica, 2021)

Detecting self-paced walking intention based on fNIRS technology for the development of BCI - Chunguang Li; Jiacheng Xu; Yufei Zhu; Shaolong Kuang; Wei Qu; Lining Sun (Medical & Biological Engineering & Computing, 2020)

Laboratory-based geoelectric monitoring of water infiltration in consolidated ground - Lining Yang; Qiang Sun; Haiping Yang (Hydrogeology Journal, 2018)

A 6-DOF parallel bone-grinding robot for cervical disc replacement surgery - Heqiang Tian; Chenchen Wang; Xiaoqing Dang; Lining Sun (Medical & Biological Engineering & Computing, 2017)

Novel adjuvant for immunization against tuberculosis: DNA vaccine expressing Mycobacterium tuberculosis antigen 85A and interleukin-15 fusion product elicits strong immune responses in mice - Li Sun; Quan Yuan; Tianhua Xu; Li Yao; Jiangmin Feng; Jianfei Ma; Lining Wang; Changlong Lv; Danan Wang (Biotechnology Letters, 2017)

Variations of Strength, Resistivity and Thermal Parameters of Clay after High Temperature Treatment - Qiang Sun; Weiqiang Zhang; Yuliang Zhang; Lining Yang (Acta Geophysica, 2016)

A porcine model of relief of unilateral ureteral obstruction: study on self-repairing capability over multiple time points - Yingying Liu; Jing Sun; Lining Miao; Lei Ji; Manyu Luo; Bing Li; Wenpeng Cui; Yangwei Wang; Yuansheng Xie; Xiangmei Chen (Molecular and Cellular Biochemistry, 2016)

Perceived reputation of others modulates empathic neural responses - Li Zheng; Qianfeng Wang; Xuemei Cheng; Lin Li; Guang Yang; Lining Sun; Xiaoli Ling; Xiuyan Guo (Experimental Brain Research, 2016)

Chronological constraints on multi-staged rapid cooling of the Tianshan Mountains inferred from apatite fission track analysis of modern river sands - LiNing Wang; JianQing Ji; DongXia Sun; QinQin Xu; BaoFu Han (Science China Earth Sciences, 2015)

A robust vision-based method for staircase detection and localization - Li Maohai; Wang Han; Sun Lining; Cai Zesu (Cognitive Processing, 2014)

Zinc Transporter 7 Induced by High Glucose Attenuates Epithelial-to-Mesenchymal Transition of Peritoneal Mesothelial Cells - Xiuli Zhang; Dan Liang; Baolei Guo; Lixia Sun; Zhi-Hong Chi; Yuan Cai; Lining Wang; Jianfei Ma (Biological Trace Element Research, 2013)

Relationship between five GLUT1 gene single nucleotide polymorphisms and diabetic nephropathy: a systematic review and meta-analysis - Wenpeng Cui; Bing Du; Wenhua Zhou; Ye Jia; Guangdong Sun; Jing Sun; Dongmei Zhang; Hang Yuan; Feng Xu; Xuehong Lu; Ping Luo; Lining Miao (Molecular Biology Reports, 2012)

sTRAIL levels and TRAIL gene polymorphisms in Chinese patients with fatty liver disease - Xiaohua Yan; Liyun Xu; Jianni Qi; Xiaohong Liang; Chunhong Ma; Chun Guo; Lining Zhang; Wensheng Sun; Jiyun Zhang; Xiaoyi Wei; Lifen Gao (Immunogenetics, 2009)

The hepatitis B virus protein MHBs(t) sensitizes hepatoma cells to TRAIL-induced apoptosis through ERK2 - Xiaohong Liang; Juan Du; Yugang Liu; Min Cui; Chunhong Ma; Lihui Han; Zhonghua Qu; Zhiyong Zhang; Zhaohui Sun; Lining Zhang; Youhai H. Chen; Wensheng Sun (Apoptosis, 2007)